KELAYAKAN USAHA TAHU PADA UD. TAHU BALI MANDIRI KECAMATAN DENPASAR BARAT KOTA DENPASAR - Evarista Meon; Ni Gst Ag Gde Eka Martiningsih; I Ketut Arnawa; Luh Putu Kirana Pratiwi (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The objectives of this study are: To analize the finansial feasibility of UD. Tahu Bali Mandiri, West Denpasar District, Denpasar city. And to find out the obtacles that exits in UD. Tahu Bali Mandiri, West Denpasar District, Denpasar City. The study was conducted at UD. Tahu Bali Mndiri, form Februasry to April 2022. The types of data used in this study are quantitative data and qualitative data. The data sourse in this study are primary data and secondary data. 4 respondents. Data coletions in this study include observation, interviews, literature study, and documentation. The results showed that the efforts made by UD. Tahu Bali Mandiri is feasible to be cultivated. This is evidenced by the calculation of the value of Net Present Value (NPV) > or Rp. 23. 877. 699.-; the value of Benefit Cost Ratio (Net B/C) is 1,71 ; The Internal Rate of Renturn (IRR) has Value 29%. Suggested UD. Tahu Bali Mandiri Enterpreneurs can try to find to other suppliers who still provide cheaper prices than what enterpreneurs usually buy from suppliers. Enterpreneurs can try to reduce the value of the profits so the don’t burden consumers know what enterpreneurs have